the The Roots of Corruption in Indonesia and Singapore: Building Real Anti-Corruption Solutions - stefie yuliandra; Abror Jilan Yankusy; Selma Dwi Anaya Pebriyanti; Aliya Sari (Journal of Ius Comparatum Law Studies, 2025)
Corruption in Indonesia is a serious problem that continues to hamper national development, undermine public trust in government, and cause huge losses to society. Although various regulations have been implemented, corrupt practices remain rampant in various sectors. This paper discusses the main causes of corruption in Indonesia, including weak oversight systems, low transparency, lack of individual integrity, permissive legal culture, and weak law enforcement. One of the root causes identified is excessive interest in material wealth, weak internal and external legal culture, and lack of transparency in financial management and public policy. The case study of the PT Pertamina Patra Niaga scandal shows gaps in the supervisory system and the ineffectiveness of regulations in preventing corruption. In comparison, Singapore's success in curbing corruption is referenced, with an emphasis on the principle of zero tolerance, the use of modern technology, monitoring of officials' assets, and public participation. From this analysis, several solutions are recommended for Indonesia, including strengthening the independence of law enforcement agencies, applying advanced technology in surveillance, increasing transparency, and providing decent salaries for public officials to reduce incentives for corruption. In conclusion, eradicating corruption requires a holistic approach that includes reforming the legal system, increasing public awareness, and strict supervision in all strategic sectors.